QUALITY AND SENSORY EVALUATIONS OF TEMPE PREPARED FROM VARIOUS PARTICLE SIZES OF LUPIN BEANS [Evaluasi Sensorik dan Kualitas Tempe dari Kacang Lupin Berbagai Ukuran Partikel] - Sri Priatni; Anastasia F. Devi; Leonardus B.S. Kardono; Vijay Jayasena (Jurnal Teknologi dan Industri Pangan, 2013)
Tempe is an Indonesian fermented soy bean, produced by using mainly Rhizopus oligosporus. Diversification of tempe raw materials is required for better food security, e.g., using lupin. The potency of lupin bean has been studied as a substitute of soy in tempe production. Nutritionally, lupin bean offers additional advantages over soy bean, i.e., it has a lower level of many anti-nutritional factors (ANFs) but contains higher protein (32-36%) than most pulses. The objectives of this study were to select the most suitable lupin bean from different particle sizes for tempe production and to characterize the quality of lupin tempe. In this study, the lupin tempe samples were analyzed for moisture content, firmness, aroma, and the total count of colony after 1 and 2 days of fermentation. Sensory evaluation was conducted by 17 Indonesian untrained panelists (hedonic) in three different days. The data were evaluated statistically using General Linear Model (GLM) and Tukey’s Honest Significant Difference (HSD). Results showed that the moisture content of lupin tempe ranged from 60 to 66%, higher than that of soy tempe (58.90%). Meanwhile, the firmness of lupin tempe was between 21.38-30.89 N. Mostly, tempes which were produced from ≤50% of particles sized ≥5 mm (L3, L5 and L6) exhibited poor quality in terms of firmness and aroma. The mean of total count of colony in lupin tempe were 3.0x104 CFU/g, lower than that of soy tempe (218x103 CFU/g), indicating a slower growth of mycelia on lupin beans. However, the overall acceptability of lupin tempe which was prepared from whole beans (L4 and L7) was not significantly different from that of soy tempe. Based on these quality and sensory tests, lupin tempe using whole lupin beans was recommended for substitute of soy bean in tempe production.